Suicidality related to first-time admissions to psychiatric hospital - Øiesvold, Terje; Bakkejord, Tony Thørring; Hansen, Vidje; Nivison, Mary; Sørgaard, Knut (Social Psychiatry and Psychiatric Epidemiology, 2012)
The epidemiology of suicidality shows considerable variation across sites. However, one of the strongest predictors of suicide is a suicidal attempt. Knowledge of the epidemiology of suicidal ideas and attempts in the general population as well as in the health care system is of importance for designing preventive strategies. In this study, we will explore the role of the psychiatric hospital in suicide prevention by investigating treated incidence of suicidal ideation and attempt, and further, discern whether sociodemographic, clinical and service utilization factors differ between these two groups at admission. The study was a prospective cohort study on treated incidence in a 1-year period and 12-month follow-up. The two psychiatric hospitals in northern Norway, serving a population of about 500,000 people, participated in the study. A total of 676 first-time admissions were retrospectively checked for suicidality at the time of admission. A study sample of 168 patients was found eligible for logistic regression analysis to elucidate the risk profiles of suicidal ideators versus suicidal attempters. GAF, HoNOS and SCL-90-R were used to assess symptomatology at baseline. 52.2% of all patients admitted had suicidal ideas at admission and 19.7% had attempted suicide. In the study sample, there were no differences in risk profile between the two groups with regard to sociodemographic and clinical factors. Males who had made a suicide attempt were less likely to have been in contact with an out-patient clinic before the attempt. The rating scales not measuring suicidality directly showed no differences in symptomatology. The findings provide evidence for the importance of the psychiatric hospital in suicide prevention. About half of the admissions were related to suicidality and the similar risk profiles found in suicidal ideators and suicidal attempters indicate that it is the ideators who mostly need treatment that get admitted to the hospital, and should be evaluated and treated with equal concern as those who ...